Unit-based Scorecards Result in Improved Bundled Resuscitation for Septic Patients in a Single Freestanding Children's Hospital. (16th November 2021) - Loberger, Jeremy M.; Hicks, Jessica; Green, Sherry; Vason, Brenda
Abstract : The Children's Hospital Association's Improving Pediatric Sepsis Outcomes (IPSO) collaborative is a multi-center quality improvement (QI) learning collaborative of 61 U.S. children's hospitals that seeks to improve sepsis outcomes through collaborative learning and reliable implementation of evidence-based interventions in pediatric emergency departments, intensive care units, general care units, and hematology/oncology units. Specifically, IPSO's goals are to decrease sepsis-attributable mortality and prevent hospital-onset sepsis among children. The following 10 abstracts represent a select group of projects undertaken by IPSO participating hospitals that were presented at one of three collaborative events in 2020 and 2021. IPSO's Research Workgroup reviewed all submitted abstracts and selected the top 10 for inclusion in this Supplement